Voter Behavior and Social Media Influence: A Case Study of Indonesia's 2024 General Election - Miarta, Wahyu Mahesa (Riwayat: Educational Journal of History and Humanities, 2024)
This study investigates the influence of social media on voter behavior during Indonesia's 2024 General Election. Through a qualitative research approach, the study employs semi-structured interviews to gather insights from 30 participants, including voters, social media influencers, and political analysts. The sampling techniques used were purposive and snowball sampling, ensuring a diverse range of respondents actively engaged in political discourse on platforms such as Facebook, Twitter, and Instagram. The research identified two key themes: (1) the democratizing potential of social media, which increases political participation, gives marginalized groups a voice, and facilitates direct engagement between voters and political figures, and (2) the negative consequences of algorithmic biases and the spread of misinformation. These biases contribute to the formation of echo chambers, where users are only exposed to content that aligns with their pre-existing beliefs, and misinformation that undermines public trust in the electoral process. The findings highlight social medias dual role as a tool for enhancing democratic engagement while simultaneously posing significant risks. The study recommends fostering algorithmic transparency, promoting digital literacy programs to help users critically evaluate information, and implementing stronger measures to combat the spread of misinformation. These steps are essential for ensuring that social media remains a positive force in the democratic process while addressing the challenges that can weaken public trust and electoral integrity.